Implementación de un control PID Fuzzy la regulación de nivel del módulo MPS PA Compact workstation mediante la tarjeta STM32F4 Discovery - Saeteros Ortiz, Célida Morelva (2018)
The present technical project is directed to the research and development of a PID-Fuzzy controller in the MPS PA workstation, for which general concepts referring to PID controllers and fuzzy logic are addressed, taking into consideration only the topics used. by this type of controllers. The programming of the PID-Fuzzy controller is developed using the Matlab software, making use of Simulink's graphic programming environment, since it allows the configuration of the parameters and variables used by the controller. For the implementation of the PID-Fuzzy controller, the MPS PA Compact Workstation plant is located in the MPS Laboratory of the Universidad Politécnica Salesiana Campus Sur. First the design of the PID and PID - FUZZY controller is made using the Matlab-Simulink software, then it is implemented with the STM32F4 Discovery card. Once the controller is implemented, the necessary data are taken to perform a comparative analysis between the PID controller and the Fuzzy. With the results obtained, it is established that the PID - FUZZY controller presents better performance in terms of its performance in the control actions; considering the design parameters: maximum peaks, stabilization time, steady state error and stability.